Формування соціальної активності студентської молоді у просторі закладу вищої освіти - Шепелєва, Наталія Володимирівна (Національний технічний університет "Харківський політехнічний інститут", 2021)
Розглядається проблема формування соціальної активності студентської молоді у просторі закладу вищої освіти. Враховуючи сучасні вектори розвитку суспільства у зв’язку з діджиталізацією, необхідним є позитивний соціальний розвиток студентів, як майбутніх лідерів. Формування їхньої соціальної активності як провідної соціальної якості потребує сприятливого простору та соціально-педагогічного спрямування. Оскільки провідним видом діяльності студентської молоді є освітня, пропонується розглянути простір закладу вищої освіти для формування їхньої соціальної активності.

The problem of the formation of student youth’s social activity in the space of a higher education institution is considered. Taking into account the modern vectors of development of society due to digitalization, it is necessary to have a positive social development of students as future leaders. The formation of their social activity, as a significant social quality, needs a favorable space and socio-pedagogical direction. Since the leading activity of student youth is educational, it is proposed to consider the space of the institution of higher education for the formation of their social activity.
Formation of student youth’s social activity in the space of higher education institution
Keywords: позанавчальний простір; діджиталізація; extracurricular space; digitalization